A baseball injury and performance initiative to combat health risks associated with early sport specialization - Balan, A.; Crotin, R. L.; Naito, R.; Escobar, D.; Zafar, A. (Strength and Conditioning Journal, 2023)
Ulnar collateral ligament (UCL) injuries have been increasing steadily for the past decade, especially among youth and adolescent amateurs. USA Baseball's Pitch Smart guidelines have been introduced to combat UCL and other throwing arm injuries because overuse is the paramount cause. Fatigue is also a major contributor to injuries. Other factors include inadequate strength, recovery methods, and parental and caregiver education. Significant misconceptions exist among parents and caregivers about UCL injury, surgical repair, strength and conditioning, and injury prevention that can directly influence their children's health and safety in sport. Therefore, parents' and caregivers' education is imperative to reduce injuries in youth baseball. This article presents an educational opportunity by providing an evidence-based training program designed to prevent injuries and maximize performance called the Baseball Injury and Performance Initiative 10 (BIPI 10). The BIPI 10 program conditions baseball players through whole-bodied movement, varying contraction tempos, and plyometrics that are sport specific. BIPI 10 is believed to offer high compliance because training can be completed daily in less than 10 minutes and initiated anywhere across competitive levels on a worldwide scale in a similar fashion to the Fédération Internationale de Football Association (FIFA) program FIFA 11+ for soccer.